The Influence of Social Training on the Empathy of Sports Pedagogue - Malinauskas, Romualdas; Malinauskienė, Vilija (Acta Paedagogica Vilnensia, 2004)
The factors of empathy of sport pedagogues are researched not sufficiently enough. The problem of the research work is that data, which would reveal the level of empathy components of sport pedagogues, is still lacking. The objective of the work is to define the influence of social training on the empathy of sport pedagogues (basing on the experience of Lithuanian Academy of Physical Education). The subject of the research is the level of empathy components of sport pedagogues. The research was based on questionnaire (Raigorodsky Empathy Scale ). The Social Skills Inventory was generated after providing an exploratory survey at Lithuanian Academy of Physical Education. The Empathy Scale demonstrated internal validity. The experiment was performed from 1998 till 2002. The experiment was performed with 230 students of the Faculty of Sport Educology, Lithuanian Academy of Physical Education, whom we divided in experimental group (136 students) and control group (94 students). In 1998 future sport pedagogues were tested. In 2002, the same investigation was repeated. The investigation was provided with the same students. With the help of x-2 test it was proved that distribution of the students in experimental group below empathy components differ statistically significant (p 0.05) before experiment and after it according to cognitive and affective empathy. By comparing evaluations of the level of empathy components with t test, it is possible to assume that the level of empathy components of sport pedagogues in experimental group differs statistically significant (p < 0.05) before experiment and after it according to cognitive and affective components of empathy.
Keywords: empathy; sports pedagogue; social training